2019
DOI: 10.7567/1347-4065/ab473d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of barrier thickness on carrier non-radiative relaxation process in InGaAs/GaAsP superlattice solar cells by piezoelectric photothermal and surface photovoltage spectroscopies

Abstract: We investigated the carrier non-radiative relaxation process of InGaAs/GaAsP superlattice (SL) solar cells with different barrier thicknesses by combining piezoelectric photothermal (PPT) and surface photovoltage (SPV) measurements. The former technique detected heat generated by non-radiative relaxation and the latter detected the surface potential change induced by the carrier accumulation. Although the mechanisms of these measurements were different, corresponding signals of the transition between the quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…No direct method to investigate the nonradiative transition was developed. We have already developed a methodology for studying the optical properties of MQW [25] and SL [10,11,26] structures. Temperaturedependent PPT measurements for InGaAs/GaAsP SL solar cells, inserting the GaAs interlayer, were carried out up to 340 K, and the electron and hole carrier transport properties were discussed [27].…”
Section: Introductionmentioning
confidence: 99%
“…No direct method to investigate the nonradiative transition was developed. We have already developed a methodology for studying the optical properties of MQW [25] and SL [10,11,26] structures. Temperaturedependent PPT measurements for InGaAs/GaAsP SL solar cells, inserting the GaAs interlayer, were carried out up to 340 K, and the electron and hole carrier transport properties were discussed [27].…”
Section: Introductionmentioning
confidence: 99%
“…The piezoelectric photothermal (PPT) technique has been adopted to investigate the non-radiative recombination of photoexcited carriers in semiconductors. [24][25][26][27] Because this technique detects heat and elastic waves caused by the nonradiative recombination, 28) a PPT signal also includes the thermal properties. In fact, Horita et al reported that the thermal properties of Si, InP and Ta were determined by photoacoustic (=photothermal) signals detected by LiNbO 3 transducer.…”
Section: Introductionmentioning
confidence: 99%